Success of Progressive Tax Policies in Reducing Income Inequality - Supriadi, Agus (Golden Ratio of Taxation Studies, 2023)
This research investigates the implications of taxation on industry competitiveness within the mining sector, aiming to provide insights into tax policy formulation and its impact on economic development. Adopting a qualitative research methodology, the study conducts a systematic literature review encompassing academic journals, government reports, and industry publications. The analysis focuses on identifying key themes, concepts, and empirical findings related to taxation in the mining industry. Through rigorous data collection and analysis, the study reveals significant insights into the multifaceted relationship between taxation, industry dynamics, and economic performance. Findings indicate that well-designed tax policies play a crucial role in shaping industry competitiveness by influencing investment behavior, operational strategies, and market incentives. However, challenges such as tax competition among jurisdictions and regulatory uncertainty pose significant hurdles to industry growth and sustainability. The research highlights the importance of balanced tax policies that prioritize industry competitiveness, environmental sustainability, and social responsibility. By fostering transparency, engaging in stakeholder consultations, and embracing evidence-based policymaking, governments can create an enabling environment for sustainable mining practices and inclusive economic growth. The study underscores the need for further interdisciplinary research to address emerging trends, evaluate policy effectiveness, and promote stakeholder collaboration in the mining sector.